Associations of Motor Performance and Executive Functions: Comparing Children with Down Syndrome to Chronological and Mental Age-Matched Controls - Thomas Jürgen Klotzbier; Benjamin Holfelder; Nadja Schott (MDPI AG, 2022)
Background. Children with Down syndrome (DS) exhibit lower motor and cognitive performance than typically developing children (TD). Although there is a relationship between these two developmental domains, only a few studies have addressed this association in children with DS compared to groups of the same chronological age (CA) or mental age (MA) within one study. This study aimed to fill this research gap. Method and Procedures. The Movement Assessment Battery for Children-2 and the Trail-Making Test was used to assess motor and cognitive performances in 12 children (M = 10.5 ± 10.08) with DS, 12 CA-matched, and 12 MA-matched controls. Results. There are significant group differences in the motor dimension (total test score; p < 0.001, η2p = 0.734), for processing speed (p < 0.001, η2p = 0.396), and cognitive flexibility (p < 0.001, η2p = 0.498). Between TD-CA and both other groups, the differences in the magnitude of correlations for the motor dimension balance are also significant (compared to DS: z = −2.489; p = 0.006, and to TD-MA: z = −3.12; p < 0.001). Conclusions. Our results suggest that the relationships depend on the studied cognitive and motor skills. It seems crucial to select a wide range of tasks for both domains that are as isolated as possible for future studies, to better understand the relationships between cognitive and motor skills in children with DS.